PERANCANGAN SISTEM RUMAH PINTAR UNTUK MENINGKATKAN KEAMANAN PENGHUNI RUMAH - Rima Rizqi Wijayanti; Ri Sabti Septarini; Syepry Maulana Husain; Abdurrasyid Abdurrasyid (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
Home Automation System is a system that is used to integrate various systems that are generally found in a house. The implementation of Home Automation System is necessary because the development of technology over time has proven to have provided many changes in people's lives. As an example of a case that requires technological development, for example, based on data from the Central Statistics Agency (BPS) there has been a crime of theft which is the most common crime experienced by households. The percentage of households experiencing theft in each province in 2012 ranged between 54%, 63-88% and 60%, while theft cases in 2013 ranged between 66%, 58-90%, and 51%. The design model used for the Home Automation System is a test that uses house model. Sensors used in this study include Light Sensors (LDR), Gas Sensors (MQ-2), Fire Sensors, Temperature and Humidity Sensors, Ultasonic Sensors, Magnetic Reed Switch Sensors, Microwave Sensors, and Obstacle Sensors. After the application of controlling the household appliances has been designed, then a system test has been made, whether it is in accordance with what is needed or there are still deficiencies in the device that have been designed. The results obtained from this study are models in the form of Home Automation System model by utilizing a mini PC Raspberry Pi, as well Android as a controller of household appliancesKeywords: Home Automation System, Raspberry PI, Android